Uptake of a colorectal cancer screening blood test is higher than of a fecal test offered in clinic: A randomized trial. (2017) - Liles, Elizabeth G.; Coronado, Gloria D.; Perrin, Nancy; Harte, Amy Howell; Nungesser, Raymond; Quigley, Neil; Potter, Nicholas T.; Weiss, Gunter; Koenig, Thomas; deVos, Theo
Abstract: Introduction: Colorectal cancer screening programs seek to maintain patient adherence to repeated tests over the duration of patients' screening eligibility. This study compares uptake of an experimental blood test with that of a FIT for colorectal cancer screening in an office setting. Methods: This small two-site randomized controlled trial (ClinicalTrials.gov, IDNCT02251782 ) assigned 413 average-risk adults overdue for screening in an integrated health system to one of two arms: Offer of a FIT versus offer of a blood test for colorectal cancer screening. The primary outcome was completion of the offered test within six weeks. Secondary outcomes were the proportion of participants with positive test results, and the proportion of participants with positive results who completed colonoscopy within 3 months of referral. Results: 99.5% (CI95: 97.3%-100%) of participants in the blood test arm and 88.1% (CI95: 83.0% − 91.8%) of participants in the FIT arm completed the offered test, a difference of 11.4% (CI95: 6.9% − 15.9%, p<.001). 16.5% of participants in the blood test arm and 1.7% of participants in the FIT arm had a positive test. 20 of 30 and 2 of 3 in the blood test and FIT arms, respectively, either scheduled or completed a colonoscopy within 3 months of the positive test result. Conclusions: Uptake of a blood test was higher than that of a FIT among participants in a randomized controlled trial. A blood test may be a useful option for those hesitant to screen with currently available tests. Graphical abstract: